Towards transforming cassava breeding: Harnessing inbred-parent-based hybrid breeding strategies - Zhang, Xiaofei; Holley, Randall; Egesi, Chiedozie Ngozi; Gemenet, Dorcus Chepkesis; Moreta, Danilo; Gimode, Winnie (Maximum Academic Press, 2024)
Genomics-assisted breeding has significantly improved recurrent selection in cassava. However, challenges persist with the use of heterozygous parents, hindering efficient trait introgression to meet the needs of ever-changing markets and environmental conditions. To address this, we propose an innovative approach – inbred-parent-based hybrid cassava breeding, aiming to transform cassava breeding by implementing backcrossing-based trait introgression, effectively purging deleterious mutations, and systematically exploring and utilizing heterosis. This perspective paper discusses the key drawbacks of heterozygous parent-based recurrent selection and outlines how the proposed approach overcomes these challenges. By leveraging the self-compatibility of cassava and advanced technologies like flower-inducing and doubled haploid technologies, along with genomics advancements and a global network, cassava breeding programs can achieve efficient, cost-effective, and accelerated inbred-parent-based hybrid breeding. In conclusion, we emphasize four crucial action areas to focus on for the initial phase to realize this transformation, i.e., understanding inbreeding depression, developing inbred or doubled haploid parents, purging genetic load, and identifying or creating heterotic pools. Through collective efforts and global collaboration, inbred-parent-based hybrid cassava breeding will transform cassava breeding and production, ensuring resilience and adaptability to significantly contribute to ending hunger and reducing poverty during the climate crisis.